Uji Efektivitas Antibakteri Ektrak Buah Belimbing Wuluh (Averrhoa bilimbi Linn) Terhadap Enterococcus faecalis - Faudah Amin, Meiny; Ariwibowo, Taufiq; Fikriyanti, Adellia (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Starfruit (Averrhoa bilimbi Linn) is fruit that many benefits. Averrhoa bilimbi Linn contain compounds of flavonoid, saponin, and triterpenoid wich have antibacterial properties. Irrigation is very important in endodontic treatment because it can eliminate pathogenic microorganisms in the root canals by applying medicaments to the root canals, because irrigation plays a role in strengthening the cleaning of determine the antibacterial effect of extract against Enterococcus faecalis Methods: The antibacterial activity was tested by well diffusion method of Averrhoa bilimbi Linn extract with concentrations of 0,1 g/mL; 0,2 g/mL; 0,3 g/mL; 0,4 g/mL; 0,5 g/mL; dan 1 g/mL as the test sample, NaOCL 5,25% as a positive control, and tween 20 as a negative control. Antibacterial activity is characterized by the formation of a clear zone around the hole of the well which called an inhibitory zone. Results: In the Averrhoa bilimbi Linn extract test against E. faecalis, a concentration of 100 g/mL was obtained which had the highest antibacterial activity on the growth of Enterococcus faecalis bacteria, which was 37.13 mm. Conclusion: Averrhoa bilimbi Linn extract effectively inhibits Enterococcus faecalis growth.